Spatiotemporal Variability and Trend Analysis of Rainfall and Temperature in Northern Nigeria - Martins Y. OTACHE; Iyanda M. ANIMASHAUN; Sadeeq A. MOHAMMED; Emmanuel O. AGBESE (FUDMA Journal of Engineering and Technology, 2025)
The consequential effects of global warming on the environment and economic sectors of every nation, particularly developing ones, have necessitated an urgent and continuous need to address the issue of climate change. This study aims to analyse the spatiotemporal variability and trends of rainfall and temperatures in Northern Nigeria. Data on rainfall and temperature for 19 meteorological stations spanning 40 years (1981-2020) were collected from the Nigeria Meteorological Agency (NiMET) for the study. For the variability assessment, descriptive statistics were employed, while linear regression, Mann-Kendall test, and Sen’s Slope estimation were used for the trend analysis. The analysis was done at different spatial and temporal scales. The results showed a significant positive trend in rainfall across all the stations, with increases of about 5.1 mm/year in the Northwest zone and 5.0 mm/year in the Northeast zone. However, the North Central zone exhibits a moderate increase of 2.0 mm/year. Additionally, the results of temperature revealed a strong upward trend, with varying levels of significance for the annual maximum (Z = 3.62), minimum (Z = 4.45), and mean (Z = 4.30) temperatures. These suggest that heat stress may be intensified and water scarcity may be exacerbated in Northern Nigeria. These findings underscore the imperative need for adaptive, resilient infrastructure and farming strategies to mitigate the impacts of climate change. The variability in rainfall and the upward trend in temperatures highlight the importance of customised, proactive measures tailored to each region’s specific climate conditions. There is a need to improve water management, promote drought-resistant crops, and establish early warning systems to enhance community resilience against the adverse effects of climate change.